2018
DOI: 10.1177/0748730418761236
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Neuroligin-1 Gene by Clock Transcription Factors

Abstract: NEUROLIGIN-1 (NLGN1) is a postsynaptic adhesion molecule involved in the regulation of glutamatergic transmission. It has been associated with several features of sleep and psychiatric disorders. Our previous work suggested that transcription of the Nlgn1 gene could be regulated by the transcription factors CLOCK and BMAL1 because they bind to the Nlgn1 gene promoter in vivo. However, whether CLOCK/BMAL1 can directly activate Nlgn1 transcription is not yet known. We thus aimed to verify whether CLOCK/BMAL1, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…mRNA extraction and qPCR. mRNA extraction, reverse transcription and qPCR procedures were performed as previously described [48][49][50] . Briefly, hippocampal mRNA was extracted using the RNeasy Lipid Tissue mini kit according to manufacturer's instructions (Qiagen, Cat No.…”
Section: Protein Extraction and Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…mRNA extraction and qPCR. mRNA extraction, reverse transcription and qPCR procedures were performed as previously described [48][49][50] . Briefly, hippocampal mRNA was extracted using the RNeasy Lipid Tissue mini kit according to manufacturer's instructions (Qiagen, Cat No.…”
Section: Protein Extraction and Western Blotmentioning
confidence: 99%
“…4444557), and primers and probes for each gene ( Table 2). Given that NLGN1 has isoforms with different properties 51 , five different probe sets were used to quantify Nlgn1 expression as previously performed [48][49][50] . Nlgn1A corresponds to the sequence containing insert A and Nlgn1B with insert B, while Nlgn1NA is a sequence without insert A and Nlgn1NB without insert B. N1gn1C corresponds to a common sequence targeting transcripts with only insert A, only insert B, both inserts and no insert.…”
Section: Protein Extraction and Western Blotmentioning
confidence: 99%
“…In Clock delta19 mice specifically, Icam‐1 expression is altered in the SCN (Wang et al., ), and the mRNA expression of EphA4 , EfnB2, and EfnA3 is decreased in the forebrain (Freyburger et al., ). Also in Clock delta19 mice, Nlgn1 showed a modified expression in a transcript variant‐dependant manner, with Nlgn1 with or without insert A showing a decreased expression, and Nlgn1 with or without insert B showing an alteration in the phase of peak expression (Hannou et al., ). Insert A is generally linked to localization of NLGN1 at inhibitory synapses, whereas insert B localizes NLGN1 at excitatory synapses (Chih, Gollan, & Scheiffele, ).…”
Section: Adhesion and Scaffolding Moleculesmentioning
confidence: 99%
“…In addition, E‐box elements have been observed in the gene of SAMs, such as E‐cadherin , EphA4 , EfnB3 , Nlgn1 , and Nlgn2 (El Helou et al., ; Freyburger et al., ; Giroldi et al., ; Hannou et al., ). Moreover, our team has shown that fragments of the promoter of both Nlgn1 and Nlgn2 are transcriptionally activated by the CLOCK/BMAL1 dimer in cell culture (Hannou et al., ), that transcriptional activation of the Nlgn1 promoter also occurs with dimers NPAS2/BMAL1 and CLOCK/BMAL2 (Hannou et al., ), and that CLOCK and BMAL1 rhythmically bind the Nlgn1 promoter region containing a canonical E‐box (CACGTG) in the mouse cerebral cortex (El Helou et al., ). Interestingly, GSK3β, a CLOCK/BMAL1 negative regulator (Sahar et al., ), decreased CLOCK/BMAL1 transcriptional activity on the Nlgn1 gene (Hannou et al., ).…”
Section: Adhesion and Scaffolding Moleculesmentioning
confidence: 99%
See 1 more Smart Citation